The anatomical studies on wood structure of trunk and branch wood of Abies spectabilis (D.Don.)Spach - Joshi, L. (Journal of Plant Resources, 2008)
The anatomical studies on wood structure of trunk and branch of six sample of Abies spectabilis collected from different localities in Nepalwere studied. The study revealed distinct growth ring, gradual transition of early wood tracheid to late wood tracheid, uniseriate or biseriate bordered pits with torus aperture. The axial parenchyma is marginal, fusiform and diffusely arranged. The fusiform parenchyma is more in branch wood than in trunk wood. Rays are uniseriate and parenchymatous. The cross field pits are taxodioid type. No differentiation was found between the trunk and branch wood structure. Bulletin of the Department of Plant Resources Vol 30, 2008 pp 71-75